Insights into the per- and polyfluoroalkyl substances-contaminated paper mill processing discharge: Detection, phytotoxicity, bioaccumulative profiling, and health risk verification. (15th January 2023) - Chow, Y.N.; Foo, K.Y.
Abstract: Per- and polyfluoroalkyl substances (PFASs), a new class of contaminants of emerging concern in different water sources and industrial discharges, have been highlighted, mainly ascribed to the high mobility, persistent, and bioaccumulative behaviors. In this work, the analytical detection of PFASs in the paper mill processing discharge (PMPD), physicochemical parameters, tannin and lignin, and phenolic content were carried out. The phytotoxicity evaluation and bioaccumulative profiles of PMPD-assisted irrigation have been conducted using a soilless cultivation system. The cytotoxicity, genotoxicity and human exposure risk were ascertained via in vitro assay on the human hepatocellular carcinoma (HepG2) cell and the estimation of daily intake, respectively. PFASs were quantitatively detected at the mean concentration of 2712.72 ng/L, consisted of mainly perfluoroalkyl carboxylic acids (PFCAs), perfluoroalkane sulfonic acids (PFSAs), perfluoroalkane sulfonamidoacetic acids (FASAAs), perfluoroalkane sulfonamides (FASAs), and fluorotelomer sulfonic acids (FTSAs). Significant reductions of the physical elongation, dry weight, and chlorophylls up to 33.49%, 31.71%, and 52.17% were recorded. Profound increase in the proline (101.81%), hydrogen peroxide (55.56%), superoxide anion (67.86%), lipid peroxidation (43.91%), and protein oxidation (32.31%), and up-regulation of antioxidant enzymes activities have been quantified. Bioaccumulation and translocation of PFASs revealed a concentration-, chain length- and functional group-dependent trend within different plant compartments. PFASs-contaminated PMPD treatments induced dose-dependent cell viability reduction and DNA damage in the HepG2 cell. The findings have highlighted that PMPD could be an underestimated source of PFASs, which represents a sharp threat to plants and public health via the water-food crop-human continuum. Future studies gearing towards the genomic profiling of PFASs in different plant species are suggested. Graphical abstract: Image 1 Highlights: Detection of per- and polyfluoroalkyl substances (PFASs) in the industrial effluent. Phytotoxicity evaluation using a hydroponic system. Distortions of physical traits and chlorophylls in the plant model. PFASs triggered oxidative stress damages and up-regulation of antioxidant enzymes. PFASs induced profound dose-dependent cytotoxicity and genotoxicity in human cell.